Pengaruh Manajemen Talenta dan Kopetensi terhadap kinerja karyawan PT. Bank Rakyat Indonesia (Persero) TBK - Firly Nur Agustiani (Jurnal Riset Perbankan Manajemen dan Akuntansi, 2019)
This study analyzes the influence of talent management on competence, the influence of competence on employee performance, and the influence of talent management on employee performance in PT. Bank Rakyat Indonesia (Persero) Tbk. Respondents of this study were taken by purposive random sampling as much as 174 respondents through a direct questionnaire. The respondents are permanent employees of PT. Bank Rakyat Indonesia (Persero) Tbk recruited through the Staff Development Program of 6.000 people. Data analysis tool used is Structural Equation Modeling (SEM) which is run through Analysis of Moment Structured (AMOS) version 20. Based on the result of research, there is positive influence between talent management to competence, competence to employee performance, and talent management to employee performance. The value of the influence of talent management on the competence of 0,92 (very strong) and significant, the value of influence of competence on employee performance of 0,19 and significant, and the value of the influence of talent management on employee performance of 0,12 and significant.